Global Change and East Asian Policy Initiatives - Shahid, Yusuf; Altaf, M. Anjum; Nabeshima, Kaoru (Washington, DC: World Bank and Oxford University Press, 2013)
Many East Asian economies have grown briskly in the past few years. However, future development will depend on the quality and timeliness of regional and national policy actions. The policy agenda must address the problems that buffeted the region in the late 1990s-associated with the weakness of domestic institutions and policies in the context of globalization. These problems include financial shocks, rapid shifts in the competitiveness of major exports, changes in international production networking, and significant reconfiguration in the geographical composition of production systems that had provided the foundation for growth. Sustaining dynamism in East Asia requires policy initiatives that contain the risks from shocks and manage the ongoing shifts and changes in ways that enhance both the competitiveness of firms and the stability of the economies. This report provides specific policy responses that could be employed to navigate successfully through periods of economic, political, and technological turbulence. The book is a collection of studies by leading experts in such fields as corporate and political governance, economic policy, globalization, higher education, legal reform, regional integration, and social protection. The studies reflect the most current thinking and research on global, regional, and national policies of relevance to East Asian economies. It is an important resource for policymakers, researchers and students interested in East Asia.